Do banks manage their flood risk exposures? Evidence from the Danish credit register - Johannes Pöschl (Danmarks Nationalbank, 2022)
Some regional banks are highly exposed to flood risk. Yet, there is little evidence that banks manage these exposures. The lack of flood risk management in these banks could worsen the adverse local economic impact of a flood. Therefore, banks should incorporate flood risk in their risk management.
Keywords: 330; Regionalbank; Kreditrisiko; Hypothek; Überschwemmung; Risikomanagement; Dänemark